Dietary Lysine Regulates Body Growth Performance via the Nutrient-Sensing Signaling Pathways in Largemouth Bass (Micropterus salmoides) - Wang, Wenqiang; Xu, Yujue; Chi, Shuyan; Yang, Peng; Mai, Kangsen; Song, Fei (Frontiers in Marine Science, 2020)
Lysine is known to be a functional nutrient from yeast to human beings. However, the mechanisms for lysine to regulate body growth and metabolism in fish species are far from fully illuminated. In order to elucidate the molecular effects of lysine on growth performance and metabolism, largemouth bass (Micropterus salmoides), which is extremely sensitive to protein composition, was chosen as the experimental model. Juvenile largemouth bass (4.16 ± 0.02 g) were fed with the lysine control diet (LC diet), the lysine supplementation diet (LS diet), and the low lysine diet (LL diet) for 8 weeks. The results showed that the LS diet group significantly increased fish growth, feed efficiency, and nutrient retention compared with those of the LL diet group in largemouth bass. Moreover, compared to the LL diet, lysine supplementation also elevated the plasma total protein, total EAA, total AA, and some individual AA concentrations. Mechanistically, lysine supplementation had a significant effect to decrease the mRNA expression levels of peptide and AA transporters induced by lysine restriction. Lysine supplementation also had an important impact on regulating the target of rapamycin (TOR) signaling pathway. More importantly, the key regulators in the amino acid response (AAR) signaling pathway were also down-regulated by lysine supplementation. Our results provide a clear elucidation of how dietary lysine affected growth performance, physiological and biochemical responses, and signaling responses and represent a sound foundation for using lysine to improve the nutrient utilization of poultry by-product meal in largemouth bass.